Mapping and Analyzing High School Physics Misconceptions: Novel Insights from a 20-Year Bibliometric Study (2002-2022) - Adrian Bagas Damarsha; Afaurina Indriana Safitri; Khoirun Nisa'; Iqbal Ainur Rizki; Nadi Suprapto; Ade Agung Harnawan (Berkala Ilmiah Pendidikan Fisika, 2023)
The primary objective of this study is to comprehensively explore, identify, and visually represent the research landscape related to physics misconceptions over the past two decades. This encompasses research trends, authorship patterns, the most prolific institutions, countries of origin, profiles of top-cited articles, and key themes through favorable keywords. It can be known which physics materials are often studied in terms of misconceptions and efforts to identify them. To fulfill this objective, a meticulous bibliometric analysis was conducted on a dataset comprising 61 meticulously selected documents, screened using specific search queries. Data were extracted from the Scopus database and analyzed using VOSviewer software.  The analysis results show that the research trend of physics misconceptions has increased in recent years. Information on authors, institutions, subject areas, countries, and most influential documents was also analyzed in the study, along with the number of citations and article production. Of paramount significance (17 clusters and 297 items) is the revelation that research in the realm of physics misconceptions gravitates towards understanding the role of technology-mediated learning, brain processes, individual student characteristics, and assessment techniques can all contribute to a better understanding of misconceptions and how they can be effectively addressed in educational settings. In essence, the implications of this research extend beyond the realm of physics education, touching on teaching methodologies, curriculum design, educational policies, and the broader advancement of scientific literacy in Indonesia.